Pelayanan Publik Aparat Pemerintah Desa Kepuh Kemiri Kecamatan Tulangan Kabupaten Sidoarjo Terhadap Kepentingan Warga Asli Dan Warga Perumahan - Soeharto Soeharto; Mulus Sugiharto (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
In Kepuh Kemiri Village at Sidoarjo district, East Java, there are two classes of citizens: indigenous and immigrant population residing in the State Housing “Anggun Sejahtera II”. In terms of public services, both two classes of the citizens are entitled to the same and equal public services provided by Village Government officials, without distinction of their status viewed from any aspect, as mandated by Law No. 25 Year 2009 on Public Services and presented by scientists criteria related to the quality of public services. The research results showed, first, to the demographic and administrative services, the village government officials not to differentiate services to indigenous and immigrant population living in Perumtas II, and second, for the provision of sanitation services and facilities funeral services, there are differences in service by government officials local villages.